Python : an introduction to programming - Parker, J. R. 1955- (ITpro collection, 2021)
This book is an introduction to programming concepts that uses Python 3 as the target language. It follows a practical just in time presentation - material is given to the student when it is needed. Many examples will be based on games because Python has become the language of choice for basic game development. Designed as a year 1 textbook for introduction to programming classes or for the hobbyist who wants to learn the fundamentals of programming, the text assumes no programming experience.